2017
DOI: 10.18632/oncotarget.14728
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs: a rising biotarget in colorectal cancer

Abstract: Colorectal cancer (CRC) is a common gastrointestinal cancer, with a high incidence and high mortality. Long non-coding RNAs (lncRNAs) are involved in the development, invasion and metastasis, early diagnosis, prognosis, the chemoresistance and radioresistance of CRC through interference with mRNA activity, directly combining with proteins to regulate their activity or alter their localization, influencing downstream gene expression by inhibiting RNA polymerase and regulating gene expression as competing endoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 128 publications
(151 reference statements)
1
50
1
Order By: Relevance
“…1, and furthermore, GSE18105 [37]: p < 0.0001, logFC = 0.91; GSE9348 [38]: p < 0.0001, logFC = 1.42) also supported its up-regulation in CRC compared to normal controls. However, it must be noted that Zhang YH et al [39] in contrast to the results of other research groups [16][17][18][40][41][42] -published underexpression of LINC00152 in CRC [39]. Our in situ hybridization results in colorectal surgical FFPE tissue sections and TMA slides revealed significant up-regulation of LINC00152 through the normal-adenoma-carcinoma sequence progression, both in epithelial and stromal cells (Fig.…”
Section: Discussioncontrasting
confidence: 61%
“…1, and furthermore, GSE18105 [37]: p < 0.0001, logFC = 0.91; GSE9348 [38]: p < 0.0001, logFC = 1.42) also supported its up-regulation in CRC compared to normal controls. However, it must be noted that Zhang YH et al [39] in contrast to the results of other research groups [16][17][18][40][41][42] -published underexpression of LINC00152 in CRC [39]. Our in situ hybridization results in colorectal surgical FFPE tissue sections and TMA slides revealed significant up-regulation of LINC00152 through the normal-adenoma-carcinoma sequence progression, both in epithelial and stromal cells (Fig.…”
Section: Discussioncontrasting
confidence: 61%
“…Lots of LncRNAs involved in the Wnt pathway are aberrantly expressed in colon cancer, for example CCAT2, CASC11, TINCR, CCAL, cir-ITCH, CTD903, and H19. 43 It is possible that these LncRNAs interrupt or counteract the function of CYTOR and the feed-forward loop. On the other hand, despite the positive feed-forward loop of CYTOR-b-catenin that exerts accelerative effects on metastasis of colon cancer, the master regulator of this loop have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have shown that miRNAs can drive the transformation from adenoma to adenocarcinoma [102], and that the micro-RNA 17/92 cluster can regulate the expression of common CRC-associated genes, including BCL3 and PTEN [103,104]. Long ncRNAs, including HOTAIR, CCAT, MALAT-1, H19, and many others, have been associated with CRC development, invasion, and metastasis and with early diagnosis and prognosis [105]. Interestingly, most lncRNAs are also associated with other cancers, suggesting that their functions span several different pathways and cell types.…”
Section: The Gut Microbiome and Non-coding Rnasmentioning
confidence: 99%